Financial Feasibility Study of Nursery Business at CV Kebun Sari, Bengkulu City - Aprilia, Dea; Edi Efrita; Novitri Kurniati; Edi Marwan (Cita konsultindo, 2026)
This study aims to analyze the feasibility of CV Kebun Sari's nursery business. The advantage of this business lies in the diversification of six cultivated commodities, so the risk of loss is smaller compared to other nurseries that only rely on one commodity. The feasibility analysis was carried out using the Net Present Value (NPV), Benefit Cost Ratio (B/C), Internal Rate of Return (IRR), and Payback Period (PP) methods. The NPV value remains positive at Rp4,857,854,973 at a bank interest rate of 10% to a discount of 51%, so the project is quite strong against the risk of increasing capital costs. In addition, the B/C Ratio value is greater than 1, namely 1.440, indicating that every Rp1 of capital produces Rp1,440 of net profit, the IRR of 51.558% is higher than the Discount Factor level of 10%, indicating very good investment returns and the Payback Period of only 4 years 6 months 7 days is much faster than the initial estimate of 5 years, reducing capital risk and accelerating investment returns. The results of the study show that CV Kebun Sari's nursery business is considered very feasible and has minimal financial risk, so this business has good prospects to be maintained and developed in the future.